2019
DOI: 10.1080/21551197.2019.1600097
|View full text |Cite
|
Sign up to set email alerts
|

Technology for Behavioral Change in Rural Older Adults with Obesity

Abstract: Background: Mobile health (mHealth) technologies comprise a multidisciplinary treatment strategy providing potential solutions for overcoming challenges of successfully delivering health promotion interventions in rural areas. We evaluated the potential of using technology in a highrisk population. Methods:We conducted a convergent, parallel mixed-methods study using semi-structured interviews, focus groups, and self-reported questionnaires, using purposive sampling of 29 older adults, 4 community leaders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…Perceived ease of use is one of the domains that has higher level in our results. This is in line with the findings of a recent study [ 40 ] and related to the fact that, while technology use has been increasing also in elderly people, they still need additional information and support to adopt it [ 41 ]. A recent study showed that commercial wearable devices are reliable for measuring physical activity level in elderly patients in real-life setting [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Perceived ease of use is one of the domains that has higher level in our results. This is in line with the findings of a recent study [ 40 ] and related to the fact that, while technology use has been increasing also in elderly people, they still need additional information and support to adopt it [ 41 ]. A recent study showed that commercial wearable devices are reliable for measuring physical activity level in elderly patients in real-life setting [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…This analysis focuses on insights about obesity stigma in three different stakeholder groups (rural, community-dwelling older adults, clinicians, and community leaders), an approach that enhances credibility via the triangulation of perspectives (Creswell et al, 2004). Full methods are previously reported (Batsis et al, 2019). Participants resided in areas designated as nonmetropolitan areas.…”
Section: Methodsmentioning
confidence: 99%
“…Weight and nutrition are key priorities in Rural Healthy People 2020 [14] as rural care is affected by lower healthcare access, [15] a complex natural and built environment, [14] healthcare provider workforce shortages, and a lack of rural-specific programs [16]. Barriers also include a need for social connectedness, access, and program availability [17]. Previous weight loss efforts in rural areas generally have been achieved through in-person interventions, phone calls, community-health workers, or peer coaching [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%